(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. It has been suggested that a dialysate calcium concentration of 1.5 mmol/L is a compromise between bone protection and cardiovascular risk. This study aimed to investigate the effect of reducing dialysate calcium concentration to 1.5 mmol/L on mineral metabolism and hemodynamic parameters. Materials and Methods. Dialysate calcium concentration was changed from 1.75 mmol/L to 1.5 mmol/L for 9 months and observed the effects on mineral metabolism and dialysis outcome parameters in 52 hemodialysis patients. Results. The results at 9 months demonstrated that postdialytic serum calcium level decreased significantly from 109 ± 7 mg/L to 102 ± 6 mg/L, intact parathyroid hormone (PTH) increased from 372 ± 52 pg/mL to 606 ± 80 pg/mL, and the oral alfacalcidol increased from 1.4 ± 0.3 µg/w to 3.3 ± 0.4 µg/w. In patients with low PTH levels, continuous increase of PTH was observed. There were no significant variation in the oral calcium carbonate dose and serum levels of alkaline phosphatase, predialytic calcium, and pre- and postdialytic phosphorus. The ultrafiltration rate and postdialysis systolic blood pressure were significantly lower after reducing the dialysate calcium concentration to 1.5 mmol/L. Intradialytic hypotension and cramps were more frequent with this dialysate calcium concentration. Conclusions. These findings demonstrated that a decrease in dialysate calcium concentration from 1.75 mmol/L to 1.5 mmol/L improved mineral metabolism by prevention of postdialytic hypercalcemia and releasing oversuppression of PTH, but it was associated with more use of oral alfacalcidol and more hemodynamic impairment.